PENENTUAN WAKTU PREVENTIVE MAINTENANCE DAN REABILITY MESIN WIRE MESH MENGGUNAKAN METODE NOMOGRAPH - Kaidah, Sri; Fernanda, Andika (Politeknik ATI Padang, 2020)
One of the things that support the smooth operation of a company is the readiness of production machines to carry out their duties. Machines are production tools formed from a series of complex systems, so they require unique and adequate maintenance planning and management. One of the industries that produce steel and wire has problems with maintenance management and supervision of its machines, such as wire mesh. machine based on the results of observation, wire machine mesh is a machine that has a high usage time. In addition, part damage is found on wire mesh machines in large quantities. So the time for Preventive Maintenance and Reliability of the Wire Mesh Machine will be determined as an improvement effort using the Nomograph method. Results above, it can be concluded that the Wire Mesh 01 machine must undergo extensive maintenance, the optimal preventive maintenance value obtained is 9.6 hours, the reliability value using periodic maintenance every 9.6 hours is 85%. One of the things that supports the smooth operation of a company is the readiness of production machines to perform their tasks. Machines are production tools formed from a series of complex systems, so they require unique and adequate maintenance planning and management. One of the industries that produce steel and wire has problems with maintenance management and supervision of its machines, such as wire mesh. machine based on the results of observation, wire machine mesh is a machine that has a high usage time. In addition, part damage is found on wire mesh machines in large quantities. So the time for Preventive Maintenance and Reliability of the Wire Mesh Machine will be determined as an improvement effort using the Nomograph method. Based on the calculation results above, it can be concluded that the Wire Mesh 01 machine must undergo extensive maintenance, the optimal preventive maintenance value obtained is 9.6 hours, the reliability value using periodic maintenance every 9.6 hours is 85%.